Peningkatan Kualitas dan Kuantitas Produk Elektroplating Melalui Perbaikan Kualitas Larutan Kimia di Bak Elektroplating dengan Filter Elektroplating - Luqman Buchori; Didi Dwi Anggoro; Dyah Hesti Wardhani (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Small electroplating industry is a small industry that is widely available in the city of Semarang. The mainprocesses in the electroplating industry are located in the coating process. This process occurs in theelectroplating bath. The quality of the metal coating is highly dependent on the quality of the chemicalsolution contained in the electroplating bath. If the chemical solution has good quality, such as the solutionwas clear, there are no impurities, the quality of the coating is also good. If the quality of the chemicalsolution is not good, then the results of the coating are also inferior such as there are bubbles in the layer, orthere is dirt on the die so that the coating process must be repeated. This will add to the cost of productionand a coating time so that increases operational costs. To solve this problem we need a system that canproduce a chemical solution that has good quality, clear, and there are no impurities. This system is calledthe filter electroplating. Results of electroplating filter application showed to increase the quantity andquality of production. The production capacity increased by 30% per day. The production turnover up 35%and profits increased by 45%. The chemical solution becomes clear and does not contain impurities so thatthe coating results becomes good.